ADAPTIVE-COMPENSATORY REACTIONS OF THE ORGANISM OF UNTRAINED ADOLESCENTS WITH DIFFERENT TYPES OF HEART RATE REGULATION TO POWER FITNESS LOAD - Chernozub, A.; Koval, V.; Derliuk, O. (Rehabilitation and Recreation, 2025)
The work aims to study adaptive and compensatory reactions of untrained adolescents with different types of heart rate regulation to various power fitness class models. Material and methods. 75 physically healthy untrained adolescents (boys aged 15–16) with identical morphometric body parameters were examined. According to the heart rate variability (HRV) results, they were divided into three groups by type of heart rate regulation: A – normotonic, B – sympathotonic, and C – vagotonic. Methods: an integral method for assessing the quantitative assessment of fitness loads, heart rate variability (HRV), and statistical analysis. The changes in the heart rate spectral analysis in study participants were determined using each of the developed models of power fitness classes. Control measurements were taken during rest and in response to a stressful stimulus sequentially applying each of the developed power fitness class models for study participants. Results. Three modes of power load regimes were developed with a clear gradation in terms of volume and intensity using different energy supply systems. On their basis, three experimental models of power fitness classes for untrained adolescents with various types of heart rhythm regulation were created. The study showed that in response to high-volume power loads in aerobic glycolysis energy supply mode (model 1), sympathetic tone (LF) increased in groups A (+14.2%) and C (+9.7%). In Group B, the influence of autonomic regulation (HF) rose by 6.9%. Using model 2, parasympathetic activity in group A adolescents decreased by 17.8% and C – by 11.5% due to a reduction in the vegetative balance index. Group B participants increased their vegetative balance by 11.9% and the central circuit of sinus rhythm regulation (VLF) by 6.9%. After using model 3, group A representatives had the most pronounced increase in sympathetic tone (LF +14.3%), and a decrease in the influence of autonomic regulation (HF -25.6%). In group C, the vegetative balance shifted towards parasympathetic regulation (LF/HF -26.4%) in response to a stressful stimulus, indicating the activation of short-term adaptation mechanisms. Conclusions. Determining the appropriate type of heart rate regulation based on spectral HRV characteristics allows for developing an effective model of power fitness classes in the shortest possible time. In adolescents with different types of heart rate regulation, depending on the variability of load mode combination and the energy supply mechanism while performing different sets of exercises, the manifestation of adaptive and compensatory reactions to the stimulus will vary.